2019
DOI: 10.33549/physiolres.933902
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D in autistic children and healthy controls

Abstract: Insufficient levels of vitamin D have been demonstrated by many authors as a risk factor for autistic patients, however, the causality has not been reliably elucidated. In the present study, levels of calcidiol were determined in group of autistic children and compared with age matched healthy children as controls. Suboptimal levels of calcidiol in more than 60 % of both autistic patients as well as of control group were found. No significant differences in vitamin D between autistic children and healthy contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Lastly, 34 eligible articles (a total of 20,580 participants) were included in the meta-analysis. Of these, 26 case-control studies [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][34][35][36][37][48][49][50] (1792 ASDs, 1969 controls) reported the blood vitamin D concentration of children and adolescents; three case-control studies [42,43,51], and two nested case-control studies [38,40] (2687 ASDs, 3574 controls) examined the neonatal vitamin D concentration of participants; one case-control study [52] and one nested case-control study [38] (517 ASDs, 642 controls) assessed maternal vitamin D concentration of the ASD and control groups; two cohort studies [39,41] (5442 neonates, 3957 pregnant women) investigated the OR/RR for ASD incidence after being exposed to early-life vitamin D deficiency or insufficiency. The participants of two articles included not only neonates but also pregnant women, so there were 36 total studies from 34 articles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, 34 eligible articles (a total of 20,580 participants) were included in the meta-analysis. Of these, 26 case-control studies [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][34][35][36][37][48][49][50] (1792 ASDs, 1969 controls) reported the blood vitamin D concentration of children and adolescents; three case-control studies [42,43,51], and two nested case-control studies [38,40] (2687 ASDs, 3574 controls) examined the neonatal vitamin D concentration of participants; one case-control study [52] and one nested case-control study [38] (517 ASDs, 642 controls) assessed maternal vitamin D concentration of the ASD and control groups; two cohort studies [39,41] (5442 neonates, 3957 pregnant women) investigated the OR/RR for ASD incidence after being exposed to early-life vitamin D deficiency or insufficiency. The participants of two articles included not only neonates but also pregnant women, so there were 36 total studies from 34 articles.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the plausible biological explanations, some epidemiological studies also reached related conclusions. A large number of case-control studies investigating the vitamin D status of children and adolescents with ASD from different countries and races showed that autistic children and adolescents had lower vitamin D status [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], but seven studies reached the opposite conclusions [32][33][34][35][36][37]. Moreover, several prospective studies investigated the role of maternal and neonatal vitamin D deficiency in autism onset.…”
Section: Introductionmentioning
confidence: 99%
“…ASD: 95.63 ± 26.63; CG: 140.43 ± 17.68 (Arastoo et al, 2018 ) Iran -Assess the serum level of vitamin D among children with ASD in the city of Ahvaz, Iran 62 ASD 84% male 31 CG 9 years 1 year -Vitamin D levels -Establish significant differences between ASD and CG levels. ASD: 9.04 ± 4.14, CG: 15.25 ± 7.89 (Bičíková et al, 2019 ) Czech Republic -Determine calcidiol levels in a group of autistic children and compared with healthy children of the same age as controls 45ASD 100% male 40 CG 4–7 years N/A -Vitamin D levels -No significant differences were found between ASD and control groups. ASD: 65.22 ± 25.950; CG: 64.46 ± 20.7 (Guo et al, 2019 ) China -Investigate vitamin A (VA) and vitamin D (VD) levels in children with autism spectrum disorders (ASD) -Determine whether VA and VD co-deficiency exacerbates clinical symptoms 332 ASD 48.5% male 197 CG 3–6 years N/A -Vitamin D levels -Vitamin D levels were lower in the ASD group than in CG -Differences in vitamin A and vitamin D accentuated the symptoms of ASD (Şengenç et al, 2020 ) Turkey -Investigate the relationship between autism spectrum disorder (ASD) and vitamin D levels in children and adolescents 100 ASD 100 CG 1529 ASD 80% male 3–18 years N/A -Vitamin D levels -Lower vitamin D levels in ASD group than in CG.…”
Section: Methodsmentioning
confidence: 99%
“…11 Meanwhile, some studies have shown that vitamin D can improve the core symptoms in ASD children. 12 A number of randomised trials showed that ASD had lower vitamin D level in different countries and races, [13][14][15][16] but several studies reached the opposite conclusions. [17][18][19] Meanwhile, A prospective research found that neonatal vitamin D was associated with the occurrence of ASD, 20 however a cohort study revealed gravida with vitamin D de ciency at mid-gestation in high risk to give birth to ASD infants while neonatal vitamin D was not associated with ASD.…”
Section: Prospero Registration Number:crd42021264097mentioning
confidence: 99%